Научные географические картоиды - Родоман (Rodoman Boris), Борис Борисович (Географический вестник=Geographical bulletin, 2017)
Объясняется понятие «географический картоид». Излагается история происхождения понятия, описываются виды картоидов и некоторые их характеристики, а также направления использования в современной географии. THE SCIENTIFIC GEOGRAPHICAL CARTOIDS (GEOGRAPHICAL SCHEMES) Explains the concept of ‘’Geographical arotids’’, also, describes the history of foundation of this concept. There are types of carotids and some of its characteristics are being looked through, as well as its use within the modern geography.